Pengaruh Pengetahuan dan Religiusitas Terhadap Keputusan dalam Berwakaf Uang di Provinsi Nusa Tenggara Barat yang di Moderasi oleh Kesadaran Berwakaf Uang - Aulani, Dina; Rois, Ihsan; Hidayat, Ali Akbar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Waqf is one of various aspects in the teachings of the Islamic religion which is based on the social and spiritual spheres. Where economic welfare and the welfare of the people are important and highly emphasized aspects, especially in cash waqf. Waqf cash is an asset intended for humanitarian donations and is intended for a long period of time. This research was conducted with the aim of analyzing the influence of people's knowledge and religiosity which is moderated by waqf awareness on decisions regarding cash waqf in West Nusa Tenggara Province. In this research, quantitative research was used using a associative approach, where non-probability sampling through a purposive sampling approach was used as a method for collecting research data. Meanwhile, it is known that the entire population of West Nusa Tenggara is not yet numerous, so this research sample was constructed using the Lemeshow formula where the research sample consisted of 100 respondents. This research uses primary data collected through questionnaires. Meanwhile, the data analysis tool uses Structural Equation Modeling (SEM) using SmartPLS 4.0 software. The results of this research show that knowledge and religion have a positive, although not significant, effect on the decision of the people of West Nusa Tenggara Province to give cash waqf, meanwhile knowledge and religion moderated by awareness have a positive and significant effect on the decision of the people of West Nusa Tenggara Province to give cash waqf.